Corporate Social Responsibility and Corporate Governance: Drivers or Hinders of Tax Aggressiveness? - Inka, Deva Ananda; Sari, Shinta Permata (Manunggal Halim Jaya, 2025)
Taxes are one of the sources of state revenue that make the most significant contribution to implementing state activities. Good corporate governance can improve a company's tax compliance. This research aims to gather empirical evidence on the relationship between corporate social responsibility, independent commissioners, audit committees, audit quality, and tax aggressiveness. This research uses a quantitative approach. Secondary data is the data used in this research, and it is obtained from the database of property and real estate companies listed on the Indonesia Stock Exchange within a period of five years, namely from 2019 to 2023. During this time interval, as many as 15 companies indexed in property and real estate are selected as research samples through purposive sampling techniques. Multiple linear regression analysis, facilitated by SPSS, was employed as a data analysis method in the research. The results of the research prove that corporate social responsibility and the audit committee do not affect tax aggressiveness, while independent commissioners and audit quality affect tax aggressiveness.